EXPANSION STRATEGIES TO DESIGN HYBRID MOLECULES OF FDA APPROVED DRUGS AS POTENTIAL INHIBITORS OF SARS Co-V-2 MAIN PROTEASE (Mpro) - THOMAS, THEJUS VARGHESE; THAKUR, AMRITA; KUMAR S., ANIL (International Journal of Applied Pharmaceutics, 2025)
Objective: This research was conducted to design hybrid molecules of FDA-approved drugs as potential inhibitors of SARS Co-V-2 (Mpro) using computational approach. Methods: This work focused on the significance of hybrid molecules or Mutual Pro-drugs. We have designed a set of 20 molecules and applied Molecular Docking, and Absorption, Distribution, Metabolism, and Excretion, Toxicity (ADMET) tests to filter them. The most effective molecule was then studied for its stability using Molecular Dynamic (MD) simulations. Results: We have found that the molecule PH-6a has a very low binding energy of-7.58kcal/mol and it forms five hydrogen bonds (Met49, Phe140, His163, and Glu166) and a pi bond (Cys145) with the crucial residues of the targeted Mpro protein. It possesses lower toxicity, is impermeable to the blood-brain barrier (BBB), and has favourable synthetic availability and drug scores. The Root mean Square Deviation (RMSD) of the lead compound (PH-6a) was within the acceptable range of 3 Å and the total energy of the compound PH-6a was determined to be-5.06 kcal/mol, indicating a higher level of stability in the structure. Conclusion: Our findings offer valuable insights into the significance of hybrid molecules and their potential application in the development of design strategies for addressing various emergency viral infections. Additionally, our results contribute to the creation of a library of compounds with potential therapeutic properties.